Thickness dependence of the strain, band gap and transport properties of epitaxial In2O3 thin films grown on Y-stabilised ZrO2(111). - Zhang, K; Lazarov, V; Veal, T; Oropeza, F; McConville, C; Egdell, R; Walsh, A (2011)
Epitaxial films of In(2)O(3) have been grown on Y-stabilised ZrO(2)(111) substrates by molecular beam epitaxy over a range of thicknesses between 35 and 420 nm. The thinnest films are strained, but display a 'cross-hatch' morphology associated with a network of misfit dislocations which allow partial accommodation of the lattice mismatch. With increasing thickness a 'dewetting' process occurs and the films break up into micron sized mesas, which coalesce into continuous films at the highest coverages. The changes in morphology are accompanied by a progressive release of strain and an increase in carrier mobility to a maximum value of 73 cm(2) V(-1) s(-1). The optical band gap in strained ultrathin films is found to be smaller than for thicker films. Modelling of the system, using a combination of classical pair-wise potentials and ab initio density functional theory, provides a microscopic description of the elastic contributions to the strained epitaxial growth, as well as the electronic effects that give rise to the observed band gap changes. The band gap increase induced by the uniaxial compression is offset by the band gap reduction associated with the epitaxial tensile strain.